Phase I trial of vorinostat added to chemoradiation with capecitabine in pancreatic cancer. Issue 2 (May 2016) - Chan, Emily; Arlinghaus, Lori R.; Cardin, Dana B.; Goff, Laura; Berlin, Jordan D.; Parikh, Alexander; Abramson, Richard G.; Yankeelov, Thomas E.; Hiebert, Scott; Merchant, Nipun; Bhaskara, Srividya; Chakravarthy, Anuradha Bapsi
Abstract: Background and purpose: This single institution phase I trial determined the maximum tolerated dose (MTD) of concurrent vorinostat and capecitabine with radiation in non-metastatic pancreatic cancer. Material and methods: Twenty-one patients received escalating doses of vorinostat (100–400 mg daily) during radiation. Capecitabine was given 1000 mg q12 on the days of radiation. Radiation consisted of 30 Gy in 10 fractions. Vorinostat dose escalation followed the standard 3 + 3 design. No dose escalation beyond 400 mg vorinostat was planned. Diffusion-weighted (DW)-MRI pre- and post-treatment was used to evaluate in vivo tumor cellularity. Results: The MTD of vorinostat was 400 mg. Dose limiting toxicities occurred in one patient each at dose levels 100 mg, 300 mg, and 400 mg: 2 gastrointestinal toxicities and one thrombocytopenia. The most common adverse events were lymphopenia (76%) and nausea (14%). The apparent diffusion coefficient (ADC) increased in most tumors. Nineteen (90%) patients had stable disease, and two (10%) had progressive disease at time of surgery. Eleven patients underwent surgical exploration with four R0 resections and one R1 resection. Median overall survival was 1.1 years (95% confidence interval 0.78–1.35). Conclusions: The combination of vorinostat 400 mg daily M–F and capecitabine 1000 mg q12 M–F with radiation (30 Gy in 10 fractions) was well tolerated with encouraging median overall survival.